Climate change education for transformation: exploring the affective and attitudinal dimensions of children's learning and action. Issue 7 (3rd July 2022) - Trott, Carlie D.
Abstract: In response to growing recognition for the mental health impacts of climate change, understanding the full range of children's psychological experiences in climate change education (CCE) contexts is critical to developing approaches that support children's constructive engagement and overall well-being. Through surveys and focus groups conducted with fifty-five children (ages 10–12), this mixed-methods study examined the affective and attitudinal impacts of a multi-site CCE program that encouraged children's learning, reflection, and action. Findings suggest that, through the program, children acquired stronger pro-environmental attitudes, a deeper respect for nature, and a greater sense of urgency towards the need for climate action. Importantly, children's negative emotions (e.g. fear, worry, anger, sadness) were mitigated by positive emotions grounded in youth-led climate action in family and community contexts. Findings are interpreted through theories of cognitive and affective transformation, which shed light on the beneficial micro- and macrolevel outcomes of children's perspective shifts.